Are there gender disparities in symptom presentation or triage of patients with chest discomfort at primary care out-of-hours services? An observational study - Yolande Appelman; Manon G. van der Meer; Karlijn H.G. Rutten; Yolanda van der Graaf; Hendrik M. Nathoe; Pieter A. Doevendans; Michelle Smit; Emmy Verheij; Anne Botermans; Frans H. Rutten (BMJ Open)
Objectives Previous hospital-based studies have suggested delayed recognition of acute coronary syndrome (ACS) in women. We wanted to assess differences in symptom presentation or triage among women and men who contacted primary care out-of-hours services (OHS) for chest discomfort.Design Retrospective observational study.Setting Primary care OHS.Participants 276 women and 242 men with chest discomfort who contacted a primary care OHS in the Netherlands in 2013 and 2014.Main outcome measures Differences between women and men regarding symptom presentation and urgency allocation.Results 8.4% women and 14.0% men had ACS. Differences in symptoms between patients with and without ACS were in general small, for both women and men. In women with ACS compared with women without ACS, mean duration of telephone calls was discriminative; 5.22 (SD 2.53) vs 7.26 (SD 3.11) min, p value=0.003. In men, radiation of pain (89.3% vs 54.9%, p value=0.011) was discriminative for ACS, and stabbing chest pain (3.7% vs 24.0%, p value=0.014) for absence of ACS . Women and men with chest discomfort received similar high urgency allocation (crude and adjusted OR after correction for ACS and age; 1.03 (95% CI 0.72 to 1.48) and 1.04 (95% CI 0.72 to 1.52), respectively). Women with ACS received a high urgency allocation in 22/23 (95.7%) and men with ACS in 30/34 (88.2%), p value=0.331.Conclusions Discriminating ACS in patients with chest discomfort who contacted primary care OHS is difficult in both women and men. Women and men with chest discomfort received similar high urgency allocation.